Nonsteroidal antiinflammatory drug-exacerbated respiratory disease: molecular mechanism, management and treatment - Ley-Tomas, J. J.; Xicotencatl-Tellez, A. M.; García-Cruz, M. L.; Jiménez-Chobillon, M. A. (Frontiers in Allergy, 2024)
It has been estimated that Nonsteroidal Anti-inflammatory drug (NSAID) Exacerbated Respiratory Disease (N-ERD) previously named as Aspirin Exacerbated Respiratory Disease (A-ERD) affects around 1.4 million persons in the United States. Its prevalence in asthmatic patients has widely been underestimated, as a considerable number of patients would need an aspirin provocation test to confirm the diagnosis. N-ERD physiopathology is somehow complex, but basically involves an imbalance in the arachidonic acid metabolite pathway. The syndrome is characterized by the presence of asthma, chronic rhinosinusitis with nasal polyposis (CRSwNP) and NSAID and aspirin intolerance. Despite maximal and comprehensive medical treatment, the disease tends to be severe, with difficult to treat asthma and highly aggressive and recurrent ethmoidal polyposis. Recently, monoclonal antibodies aimed at reducing type 2 inflammation have demonstrated very promising results on disease control. The goal of this review is to provide the most recent published advances and evidence on physiopathology, diagnostic protocols and therapeutic strategies of N-ERD.